The effect of some stimuli used in teaching perspective on the sensory perception of the third dimension of geometric shapes (Journal of the College of Basic Education, 2022)
Some argue that individuals differ in their sensory perceptions according to their exposure to stimuli, and this is due to environmental factors or the difference in scientific levels or their golden capabilities, which results in a difference in the degrees of changing their behavior (i.e. their learning). (Qatami, 1989, p. 15). Therefore, education is presented as a change in behavior that results from practice and experience to learn. This learning can be measured by measuring the change made by the learner from the state in which the educational situation began. Therefore, the progress of these measurements is evidence of behavior change.